Situation and Efficiency in Management of Financial and Health Resources Management in Wang Chin Hospital Fiscal, Year 2550 - Boonumpun, Supachai (Journal of Health Science of Thailand, 2018)
This retrospective descriptive study investigated the efficiency of budget management and health resources conditions in Wang Chin Hospital. The objective of this study was to a evaluate the efficiency of budget management under the Universal Health Care (UC) with respect to financial and health resources conditions, revenue and expenditure statements, cash-flow management, reserve assets, resources use services, quality of accounting data on accrual basis, based on financial reports (0110 รง 5) of the hospital and compared with the financial indexes of the Public Health Ministry. The Study found that the Universal Health Care Coverage accounting for78.94 percent of the total population in the health region and receiving 516.85 baht per person-year based on the UC-population only and 405.34 baht on the average. It, hence covered the out-patient services, served the inpatient, health promotion and protection and other operating costs. However, the allocations varied unsystematically from province to province and in each district depended on their public health coordinating committee, operated with 5 procuring units. Creditors bookings were not systematized nor efficient. Medical supplies were not always as planned and arranged by both the hospitals and the service network within the district. Financial analysis, during fiscal years 2548-2550, applied indices in monitoring of financial liquidity, resources use efficiency administration, cost management efficiency and not profit margin excluding depreciation and amortization). Negative results were reported annually while liquidity remained in level 8 or critical. Additional financial analysis of the hospital confirmed years of poor liquidity, affecting the working capital without adequate input of financial assistance to cope with the growing debts annually. The condition, therefore, calls for timely financial aid and close surveillance. Also health manpower development for all and development of financial and resources management systems of the network are badly needed in order to maximize their services efficiency thus supposed to the arrangement culls the budget or, the assistance by use the correct information, and have the anticipation something stability position has of the hospital all the time, participate inly in planning develops an organization, very have data system every in time a side, develop every level officer in the organization, and arrange finance system and the resource of the network, for work public health administration efficiently for, be effective affect build public health serve least.